Not all credit is created equal: Mortgage vs non-mortgage debt and private saving rate in Turkey - Cengiz Tunc; Abdullah Yavas (Central Bank Review (CBR), 2016)
The private saving rate in Turkey has decreased substantially since 2000. In this study, we investigate the determinants of the private saving rate in Turkey, with a special focus on the role of mortgage debt. We find a strong and robust negative effect of mortgage credit growth on private saving rate. Non-mortgage consumer credit growth also has a negative and robust effect on private saving rate, though its effect is smaller than that of mortgage credit. Business credit growth, on the other hand, has a positive impact on private saving rate. Our results provide strong support for the argument that the high growth rate of consumer credit is a primary reason for the recent decrease in private saving rate in Turkey. We also find that private saving rate displays strong persistence, and public saving rate partially crowds out private saving rate. In addition, per capita real income growth rate and macroeconomic uncertainty have positive impact on private saving rate.
Keywords: 330; Saving; Mortgage debt